New Insights on the Role of Lipid Metabolism in the Metabolic Reprogramming of Macrophages - Batista-Gonzalez, Ana; Vidal, Roberto; Criollo, Alfredo; Carreño, Leandro J. (Frontiers in Immunology, 2020)
Macrophage activation is intimately linked to metabolic reprogramming. Inflammatory (M1) macrophages are able to sustain inflammatory responses and to kill pathogens, mostly by relying on glycolysis and fatty acid biosynthesis. Glycolysis is a swift way of producing ATP, and fatty acids serve as precursors for the synthesis of inflammatory mediators. On the opposite side, anti-inflammatory (M2) macrophages mediate the resolution of inflammation and tissue repair, switching their metabolism to fatty acid oxidation and oxidative phosphorylation. Over the years, this classical view has been challenged by recent discoveries pointing to a more complex metabolic network during macrophage activation. Lipid metabolism plays critical roles in the activation of both M1 and M2 macrophages. Recent evidence shows that fatty acid oxidation is also essential for inflammasome activation in M1 macrophages, and glycolysis is now known to fuel fatty acid oxidation in M2 macrophages. Ultimately, targeting lipid metabolism in macrophages can improve the outcome of metabolic diseases. Here, we review the main aspects of macrophage immunometabolism form the perspective of the metabolism of lipids. Building a reliable metabolic network during macrophage activation will bring us closer to targeting macrophages for improving human health.